Disruption of Alfvenic turbulence by magnetic reconnection in a collisionless plasma - Mallet, A; Schekochihin, AA; Chandran, BDG (Cambridge University Press, 2017)
We calculate the disruption scale λD at which sheet-like structures in dynamically aligned Alfvénic turbulence are destroyed by the onset of magnetic reconnection in a low-β collisionless plasma. The scaling of λD depends on the order of the statistics being considered, with more intense structures being disrupted at larger scales. The disruption scale for the structures that dominate the energy spectrum is λD ∼ L 1/9 ⊥ (deρs) 4/9 , where de is the electron inertial scale, ρs is the ion sound scale and L⊥ is the outer scale of the turbulence. When βe and ρs/L⊥ are sufficiently small, the scale λD is larger than ρs and there is a break in the energy spectrum at λD, rather than at ρs . We propose that the fluctuations produced by the disruption are circularised flux ropes, which may have already been observed in the solar wind. We predict the relationship between the amplitude and radius of these structures and quantify the importance of the disruption process to the cascade in terms of the filling fraction of undisrupted structures and the fractional reduction of the energy contained in them at the ion sound scale ρs . Both of these fractions depend strongly on βe , with the disrupted structures becoming more important at lower βe . Finally, we predict that the energy spectrum between λD and ρs is steeper than k −3 ⊥ , when this range exists. Such a steep ‘transition range’ is sometimes observed in short intervals of solar-wind turbulence. The onset of collisionless magnetic reconnection may therefore significantly affect the nature of plasma turbulence around the ion gyroscale.